2013
DOI: 10.1371/journal.pone.0057139
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Photoacclimation in Twelve Freshwater Photoautotrophs (Chlorophyte, Bacillaryophyte, Cryptophyte and Cyanophyte) Isolated from a Natural Community

Abstract: Different representative of algae and cyanobacteria were isolated from a freshwater habitat and cultivated in laboratory to compare their photoacclimation capacity when exposed to a wide range of light intensity and to understand if this factor may modify natural community dominance. All species successfully acclimated to all light intensities and the response of phytoplankton to increased light intensity was similar and included a decrease of most photosynthetic pigments accompanied by an increase in photopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 64 publications
0
32
0
Order By: Relevance
“…There are two explanations for an increase in a in metalimnion. Either it can be due to physiological acclimation in the phytoplankton (Grobbelaar et al 1995;MacIntyre et al 2002;Deblois et al 2013) or it can be due to an increase in biomass of phytoplankton in this zone (Amand and Carpenter 1993;Hamilton et al 2010). To explore whether the higher metalimnetic a values were dictated by higher levels of phytoplankton biomass with depth, we examined daily profiles of Chl a fluorescence measured in Vedsted Lake.…”
Section: Discussionmentioning
confidence: 99%
“…There are two explanations for an increase in a in metalimnion. Either it can be due to physiological acclimation in the phytoplankton (Grobbelaar et al 1995;MacIntyre et al 2002;Deblois et al 2013) or it can be due to an increase in biomass of phytoplankton in this zone (Amand and Carpenter 1993;Hamilton et al 2010). To explore whether the higher metalimnetic a values were dictated by higher levels of phytoplankton biomass with depth, we examined daily profiles of Chl a fluorescence measured in Vedsted Lake.…”
Section: Discussionmentioning
confidence: 99%
“…A similar effect is observed in Hartbeespoort for accessory pigments allophycocyanin (AP C = 11.2 × chla 0.59 , r 2 = 0.68, N = 34) and pheophytin (P heo = 0.16×chla 0.9522 , r 2 = 0.95, N = 38). Accessory pigments are modulated either by high light and nutrient exposure (e.g., [63]) or through other physiological processes reflected by changes in gross biomass. The equations for the PC:chl-a ratio versus chl-a were derived mathematically from the power-law function and are, therefore, not a result of "spurious correlation" [64].…”
Section: Tchl-specific Phytoplankton Absorptionmentioning
confidence: 99%
“…This effect might be related to nitrogen limitation as cell abundance increases [65]; however, nutrient data acquired simultaneously reveal no shortage of total nitrogen (or other nutrients) associated with reduced PC:chl-a ratios ( Figure 17C). An alternative explanation is that phycobilipigment production is reduced in high light, shallow mixed surface scum layers [63,66] or in fast growth scenarios. While a precise explanation for this effect remains somewhat unknown, the observation has some important implications for extremely high biomass and surface scum scenarios.…”
Section: Tchl-specific Phytoplankton Absorptionmentioning
confidence: 99%
“…To calculate Z c , we adopted E c (PAR) based on the freshwater phytoplankton minimum light requirement described by Deblois et al [47]. The authors reported that Chlamydomonas sp.…”
Section: Critical Depth For Photosynthesismentioning
confidence: 99%
“…(Chlorophyta) (identified in this study) shows a growth rate close to zero when exposed to irradiance of 14 µEm −2 s −1 , whereas other species, such as Aulacoseira granulate (diatom) and Cryptomonas obovata (Cryptophyta), present a growth rate of up to 0.2 divisions/day when exposed to the same light regime. For freshwater phytoplankton communities, a minimum E c of 14 µEm −2 s −1 was defined as a general compensation irradiance as described in Deblois et al [47] and therefore used as input to calculate Z c in Equation (9). Furthermore, analyses of critical depth must take into account the depth of the mixing layer (Z m ).…”
Section: Critical Depth For Photosynthesismentioning
confidence: 99%